The more, the merrier? Obligate symbiont density changes over time under controlled environmental conditions, yet holds no clear fitness consequences. (11th January 2017) - Parkinson, Jasmine F.; Gobin, Bruno; Hughes, William O. H.
Abstract: Symbiotic bacteria are highly diverse, play an important role in ecology and evolution, and are also of applied relevance because many pest insects rely on them for their success. However, the dynamics and regulation of symbiotic bacteria within hosts is complex and still poorly understood outside of a few model systems. One of the most intriguing symbiotic relationships is the obligate, tripartite nutritional mutualism in sap‐feeding, economically‐destructive mealybugs (Hemiptera: Sternorrhyncha: Pseudococcidae), which involves γ‐proteobacteria hosted within β‐proteobacteria hosted within the mealybugs. The present study examines whether there is population variation in symbiont density (i.e. infection intensity, or titre) in the citrus mealybug Planococcus citri (Risso) and how this impacts host life‐history. Symbiont density is found to differ significantly between populations when reared under controlled environmental conditions, indicating that the density of symbiont infections is influenced by host or symbiont genotype. However, symbiont density changes in populations over multiple generations, indicating that symbiont densities are dynamic. Surprisingly, given that the symbionts are essential nutritional mutualists, the density of the symbionts does not correlate significantly with either host fecundity or development. Higher levels of symbionts have no clear benefit to hosts and therefore appear to be superfluous, at least under constant, optimized environmental conditions. Excessive symbiont density may be an evolutionary artefact from a period of inefficient vertical transmission when the balance of conflict between host and symbiont was still being established.